2017
DOI: 10.1002/lary.26727
|View full text |Cite
|
Sign up to set email alerts
|

Social media presence of otolaryngology journals: The past, present, and future

Abstract: NA. Laryngoscope, 128:363-368, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…Studies carried out in other scientific areas have reported similar findings, in emergency medicine publications, a positive correlation was found between the number of citations and alternative metrics for measuring the impact factor [9]. Moreover, scientific publications of otolaryngology [10] have demonstrated the potential of social networks for sharing search, increasing the number of readers, and promoting discussions regarding scientific articles. These data suggest that the information provided by both kinds of metrics is complimentary.…”
Section: More Information Can Be Found In Supplementarysupporting
confidence: 58%
“…Studies carried out in other scientific areas have reported similar findings, in emergency medicine publications, a positive correlation was found between the number of citations and alternative metrics for measuring the impact factor [9]. Moreover, scientific publications of otolaryngology [10] have demonstrated the potential of social networks for sharing search, increasing the number of readers, and promoting discussions regarding scientific articles. These data suggest that the information provided by both kinds of metrics is complimentary.…”
Section: More Information Can Be Found In Supplementarysupporting
confidence: 58%
“…12 Previous literature suggests that increased presence and positive perceptions on social media have been associated with academic influence, patient satisfaction, and even 30-day mortality rate. 13,14 Oyewumi et al 15 recently reported that individual otolaryngology clinicians have a presence on social media, but were unsure how to capitalize on the benefits of this communication method. Given the high interest and use of social media by the general public, it is important to consider the accessibility of health care organizations on social media.…”
mentioning
confidence: 99%
“…One study identified that as of 2017, six of the top 12 plastic surgery journals had a Twitter account, with an increase in their impact factor after they joined Twitter (Asyyed et al, 2019). This has also been described in the ENT and orthopedic surgery literature (Hughes et al, 2017;Wong et al, 2018). When searching the top journals in surgery based on impact factor, 9 of the top 10 journals have an official Twitter account (Scimago Institutions Rankings, 2019).…”
Section: Discussionmentioning
confidence: 95%